2021
DOI: 10.7554/elife.73062
|View full text |Cite
|
Sign up to set email alerts
|

The LRRK2 G2019S mutation alters astrocyte-to-neuron communication via extracellular vesicles and induces neuron atrophy in a human iPSC-derived model of Parkinson’s disease

Abstract: Astrocytes are essential cells of the central nervous system, characterized by dynamic relationships with neurons that range from functional metabolic interactions and regulation of neuronal firing activities, to the release of neurotrophic and neuroprotective factors. In Parkinson's disease (PD), dopaminergic neurons are progressively lost during the course of the disease, but the effects of PD on astrocytes and astrocyte-to-neuron communication remains largely unknown. This study focuses on the effects of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 96 publications
2
37
0
Order By: Relevance
“…Astrocyte atrophy was found in the derived astrocytes from PD patients with LRRK2 G2019S mutation (Table 1; Ramos-Gonzalez et al, 2021). LRRK2 G2019S mutated astrocyte from hiPSC appeared to cause nutritional damage to the DAergic neurons, damage the ATP supply, lowmitochondrial density, and ER disorder (de Rus Jacquet et al, 2021). Moreover, autophagy dysfunction was observed in astrocytes derived from LRRK2 G2019S mutated iPSCs (di Domenico et al, 2019; Figure 1).…”
Section: Leucine-rich Repeat Kinase 2 and Astrocytesmentioning
confidence: 99%
“…Astrocyte atrophy was found in the derived astrocytes from PD patients with LRRK2 G2019S mutation (Table 1; Ramos-Gonzalez et al, 2021). LRRK2 G2019S mutated astrocyte from hiPSC appeared to cause nutritional damage to the DAergic neurons, damage the ATP supply, lowmitochondrial density, and ER disorder (de Rus Jacquet et al, 2021). Moreover, autophagy dysfunction was observed in astrocytes derived from LRRK2 G2019S mutated iPSCs (di Domenico et al, 2019; Figure 1).…”
Section: Leucine-rich Repeat Kinase 2 and Astrocytesmentioning
confidence: 99%
“…Over the past years, multiple studies from independent laboratories have demonstrated that hiPSC modeling is a powerful tool for uncovering the role of astrocytes in CNS diseases, including AD ( Oksanen et al, 2017 ; Preman et al, 2021 ; de Leeuw et al, 2022 ), Parkinson’s disease ( di Domenico et al, 2019 ; de Rus Jacquet et al, 2021 ; Ramos-Gonzalez et al, 2021 ; Russ et al, 2021 ; Trudler et al, 2021 ) and amyotrophic lateral sclerosis ( Birger et al, 2019 ; Zhao et al, 2020 ; Szebényi et al, 2021 ; Ziff et al, 2021 ; Giacomelli et al, 2022 ). Developing human models is particularly critical since such diseases cannot be fully recapitulated in animal systems and thus require multiple integrated approaches (i.e., combination of human and animal studies) to understand their pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the CRISPR revolution has provided the means to reproduce and study pathological protein variants within meaningful and physiologically relevant contexts ( Freedman et al, 2015 ; Ponomareva et al, 2016 ) as well as perform targeted rescue of disease-causing mutations in model systems ( Min et al, 2020 ). These developments become synergistic with the possibility of reprogramming patient-derived induced Pluripotent Stem Cells (iPSCs) to study cell biological behavior of mutated variants expressed at endogenous levels in disease-relevant cell types and organoids ( Parfitt et al, 2016 ; Boutry et al, 2018 ; Dvela-Levitt et al, 2019 ; Flemming et al, 2020 ; De Rus Jacquet et al, 2021 ; Romano et al, 2021 ).…”
Section: Candidate Components For An Updated Multidisciplinary Toolbo...mentioning
confidence: 99%